PERKEMBANGAN DAN PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK MELALUI MODEL PEMBELAJARAN THINK TALK WRITE - Andika Tanca Sandi; Yarman Yarman; Fitrani Dwina; Khairani Khairani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Mathematical communication is an essential competency in mathematics learning; however, the mathematical communication skills of Grade VIII students at SMP Negeri 25 Padang were still relatively low. This study aimed to describe the development of students' mathematical communication skills during the implementation of the Think Talk Write (TTW) cooperative learning model and to determine whether these skills were better than those of students who learned through conventional instruction. This study employed a quasi-experimental method using a nonequivalent posttest-only control group design. The research samples were Class VIII.6 as the experimental group and Class VIII.7 as the control group. Data were collected through quizzes and an essay-based mathematical communication skills test. The results showed that the mathematical communication skills of students in the experimental class improved progressively throughout the implementation of the TTW learning model. The Mann–Whitney test at a significance level of 0.05 yielded a p-value of 0.000, leading to the rejection of H₀. Therefore, students who learned through the Think Talk Write cooperative learning model demonstrated better mathematical communication skills than those who received conventional instruction.   Keyword: mathematical communication skills; cooperative learning model; think talk write.   Abstrak: Kemampuan komunikasi matematis merupakan salah satu kompetensi penting dalam pembelajaran matematika, namun kemampuan tersebut pada peserta didik kelas VIII SMP Negeri 25 Padang masih tergolong rendah. Penelitian ini bertujuan untuk mendeskripsikan perkembangan kemampuan komunikasi matematis peserta didik selama diterapkan model pembelajaran kooperatif tipe Think Talk Write (TTW) serta mengetahui perbedaannya dengan peserta didik yang belajar menggunakan pembelajaran konvensional. Penelitian menggunakan metode eksperimen semu (quasi experiment) dengan rancangan nonequivalent posttest-only control group design. Sampel penelitian terdiri atas kelas VIII.6 sebagai kelas eksperimen dan kelas VIII.7 sebagai kelas kontrol. Data dikumpulkan melalui kuis dan tes kemampuan komunikasi matematis berbentuk soal uraian. Hasil penelitian menunjukkan bahwa kemampuan komunikasi matematis peserta didik pada kelas eksperimen mengalami peningkatan secara bertahap selama penerapan model TTW. Hasil uji Mann-Whitney pada taraf signifikansi 0,05 menghasilkan p-value = 0,000 sehingga H₀ ditolak. Dengan demikian, kemampuan komunikasi matematis peserta didik yang belajar menggunakan model pembelajaran kooperatif tipe Think Talk Write lebih baik daripada peserta didik yang belajar menggunakan pembelajaran konvensional.   Kata kunci: kemampuan komunikasi matematis; model pembelajaran kooperatif; think talk write.